If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5y + -4y + 9x + 2 = 0 Reorder the terms: 2 + 3x + 9x + -5y + -4y = 0 Combine like terms: 3x + 9x = 12x 2 + 12x + -5y + -4y = 0 Combine like terms: -5y + -4y = -9y 2 + 12x + -9y = 0 Solving 2 + 12x + -9y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + 12x + -2 + -9y = 0 + -2 Reorder the terms: 2 + -2 + 12x + -9y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 12x + -9y = 0 + -2 12x + -9y = 0 + -2 Combine like terms: 0 + -2 = -2 12x + -9y = -2 Add '9y' to each side of the equation. 12x + -9y + 9y = -2 + 9y Combine like terms: -9y + 9y = 0 12x + 0 = -2 + 9y 12x = -2 + 9y Divide each side by '12'. x = -0.1666666667 + 0.75y Simplifying x = -0.1666666667 + 0.75y
| 2xa-11=-5 | | 5x=48+2x | | (5x+3o)+9o= | | -3(4)+-2=x | | -(x-1)-4(x-3)=58 | | -0.2(-15x-10)=10 | | -7(4)+15=x | | z(2z-9)(z+4)=0 | | x^2+kx-9=0 | | 5=4(x-4)+3-3x | | 30+y=3y | | 12x+4+13x-4=180 | | (m-1)x^2+mx+2m=0 | | n+(n+1)+(n+2)+(n+3)=1368 | | 30+y=6y | | 6x+8-5x=14-15x-16 | | 6x/5+12x=3(5/2) | | 3b^2+20b+31=6 | | x^4+10x^3-59x^2+40x+60=0 | | 12y-8=-4 | | 34x-543=321 | | 2x-34=87 | | 29x^2+10x-21=0 | | 3=3(x-2)+5-2x | | (14y+11)+(-4y-3)= | | 15=5(x+9) | | 13p+16q+p-5q-7p= | | 2x(4x-1)=7 | | (14y+11)+(14y-3)= | | 5-9x=35-23x | | D=Bgx | | 0.8x+6.7=2.3 |